Crafting Power, Piety, and Memory: The Sabil-Maktab of 'Abd al-Rahman Katkhuda in Bayn al-Qasrayn, Cairo (1157 AH/ 1744 CE) - Al-Shamy, Nehal Hany (AUC Knowledge Fountain, 2026)
Among hundreds of sabil-maktabs in Cairo, the one ʿAbd al-Rahman Katkhuda built in Bayn al-Qasrayn in 1157/1744 stands out as an iconic jewel, rising to be a symbol of the city itself. However, this sabil is more than just a beautiful building, for its beauty was only a means to channel political, commemorative, and spiritual connotations. This thesis is concerned with analyzing the raisons d’être of constructing the sabil through investigating the historical and political circumstances that influenced its patron at the time, and their reflections in the artistic choices he made. I argue that crafting the sabil as a landmark, by exploiting a strategic location and investing in a lavish, extraordinary decorative program, was a deliberate decision to convey two strands woven together: highlighting the political and financial capabilities of the aspiring ʿAbd al-Rahman al-Qazdughli, and commemorating an auspicious religio-political moment central to his ascension to power, which is crystallized in the Hajj journey he performed in 1151/1739. The broader aim of this thesis is to utilize the sabil as a case study to argue against a persistent claim that has long marginalized Ottoman architecture in Egypt, which is considering Egypto-Ottoman architecture as a rigid copy or pastiche of Mamluk architecture. The sabil provides, in this regard, an excellent opportunity to explore the dynamic and creative process of designing Egypto-Ottoman architecture, where hallmarks from both the Mamluk and Ottoman empires were actively assimilated to represent historicity and contemporaneity, while echoing the trends of a changing world. Moreover, analysis of the textual and visual evidence can refute the nationalist and Orientalist arguments that dismissed Egypto-Ottoman architecture in Cairo as “foreign,” based on classifications that employed imaginary ethnic attributions. This thesis, therefore, aspires to invite readers to reconsider what constitutes Egyptian and Ottoman heritage, and opens questions about the complex political, religious, and social purposes, which fueled the flourishing architectural patronage in Egypt during the eighteenth century.